Materials physics and chemistry : applied mathematics and chemo-mechanical analysis - Singh, Satya Bir; Vakhrushev, Alexander V.; Haghi, A. K. (Burlington, ON, Canada ; Palm Bay, Florida : Apple Academic Press Inc., 2021)
"This volume focuses on the development and application of fundamental concepts in mechanics and physics of solids as they pertain to the solution of challenging new problems in diverse areas, such as materials science and micro- and nanotechnology. In this volume, emphasis is placed on the development of fundamental concepts of mechanics and novel applications of these concepts based on theoretical, experimental, or computational approaches, drawing upon the various branches of engineering science and the allied areas within applied mathematics, materials science, and applied physics. Introducing and demonstrating the utility of computational tools and simulations, this volume provides a modern view of how solids behave, how they can be experimentally characterized, and how to predict their behavior in different load environments. It discusses recent developments and compares them to classical theories along with introducing readers to the current state of the art in predicting failure using a combination of experiment and computational techniques. Materials Physics and Chemistry: Applied Mathematics and Chemo-Mechanical Analysis emphasizes the basics, such as design, equilibrium, material behavior, and geometry of deformation in simple structures or machines. Readers will find a thorough treatment of stress, strain, and the stress-strain relationships. Meanwhile it provides a solid foundation upon which readers can begin work in composite materials science and engineering. Many chapters include theory components with the equations students need to calculate different properties. Key features: Emphasizes using math to solve engineering problems instead of focusing on derivations and theory Encompasses the full range of applied mathematics and engineering from modeling to solution, both analytical and numerical. Develops a framework for the equations and numerical methods of applied mathematics"--
Chapter 11: Simultaneous Optimization Aspects in Industrial Gas Sweetening Process for Sustainable Development -- Chapter 12: A DFT Study of CuNFe (N = 1-5) Nanoalloy Clusters -- Chapter 13: Nanotechnology as a Clean Technology and a Vision for the Future -- Chapter 14: Wear Studies on Aluminum Metal Matrix Composite Prepared from Discarded Tea Extract and Coconut Shell Ash Particles -- Chapter 15: Study on Fretting Wear Characteristics of Aluminum-Based Metal Matrix Hybrid Composites Fabricated by Friction Stir Welding Technique -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Materials science -- Mathematical models; MATHEMATICS / Applied; SCIENCE / General; SCIENCE / Chemistry / General